Unintended consequences of QE: Real estate prices and financial stability - Tobias Berg; Rainer Haselmann; Thomas Kick; Sebastian Schreiber (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2023)
We investigate how unconventional monetary policy, via central banks' purchases of corporate bonds, unfolds in credit-saturated markets. While this policy results in a loosening of credit market conditions as intended by policymakers, we report two unintended side effects. First, the policy impacts the allocation of credit among industries. Affected banks reallocate loans from investment-grade firms active on bond markets almost entirely to real estate asset managers. Other industries do not obtain more loans, particularly real estate developers and construction firms. We document an increase in real estate prices due to this policy, which fuels real estate overvaluation. Second, more loan write-offs arise from lending to these firms, and banks are not compensated for this risk by higher interest rates. We document a drop in bank profitability and, at the same time, a higher reliance on real estate collateral. Our findings suggest that central banks' quantitative easing has substantial adverse effects in credit-saturated economies.
Keywords: 330